A cidade é o suporte: arte urbana, mercado e subversão - Visini, Débora Machado (2017)
The reflections brough there use the relationship between art / city as na observatory and start from a political conviction that the space of the city should be a space for the realization of public life and commitment with the different. In this sense, the theme art and city is though to symbiotic way involving as artistic interventions that are made in the urban space, the urban art. The research accompanying the movement of the city, a stage of political, social and economic actions that move in the processes of commercialization and differentiation, after all the urban space as an art, are inserted within a system of production. Initially we observed a process of accommodation of art in the market, however, at another time we experienced urban artistic initiatives that oppose the economic system. Problematizations are broughtaboutby a theoretical bias and culminate in anartistic action in urban space. In fact, the urban art, a phenomenon that happens on a global scale, leads our thinking towards a local event, held in the city of João Pessoa. In this context, we thematize women in urbanspace as anargument for a practical action performed, emphasizing a process of sexual differentiation, using na urban art as a tool of subversion and empowerment.